FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Febryanthi, Sherlina; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to examine some factors i.e. profitability, leverage, liquidity, firm size, public accounting firm reputation, auditor opinion, and firm age which gives influence to the timeliness of the submission of financial statement. This research is a quantitative research, the population is manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2016 periods. The sample collection has been done by using purposive sampling technique and 9 companies which have met the criteria have been selected as samples and 45 observations has been obtained. The data analysis technique has been carried out by using multiple linear regressions. Based on the result of the test, it can be concluded that profitability gives negative influence to the timeliness of the submission of financial statement, leverage gives positive influence to the timeliness of the submission of financial statement, liquidity gives positive influence to the timeliness to the submission of the financial statement, firm size does not give any influence to the submission of financial statement, public accountancy firm reputation does not give any influence to the timeliness of the submission of financial statement, and firm age does not give any influence to the timeliness of the submission of financial statement.Keywords: Profitability, leverage, liquidity, company size, auditors opinion